Endoscopic and Robotic Parotidectomy for the Treatment of Parotid Tumors: A Systematic Review and Meta-Analysis - Chen, Shanwen; Zhao, Mei; Wang, Dong; Zhao, Yi; Qiu, Jianxin; Liu, Yehai (Frontiers in Oncology, 2021)
Background The goal of this review was to introduce endoscopic/robotic parotidectomy (EP/RP) and compare EP/RP against conventional parotidectomy (CP) regarding the intraoperative and postoperative parameters in the treatment of parotid tumors. Methods A systematic literature search of medical databases (PubMed, Embase, and Cochrane Central Register of Controlled Trials) was performed from inception to November 2020 to generate relevant studies. Results A total of 13 eligible studies (572 patients) were included for systematic review, and 7 out of 13 comparable studies for the quantitative synthesis of outcomes. Patients who underwent EP were characterized by less intraoperative bleeding volume, shorter incision length, and higher satisfaction postoperatively (WMD, 95% CI, -42.80; - 58.23 to -27.37; p < 0.01; WMD, 95% CI, -5.64; -7.88 to -3.39; p < 0.01; SMD, 95% CI, 1.88; 1.46 to 2.31; p < 0.01, respectively). However, operative time and risk of facial palsy exhibited no significant differences (WMD, 95% CI, -11.17; -26.71 to 4.34; p = 0.16; OR, 95% CI,0.71; 0.39 to 1.32; p = 0.28, respectively). Conclusions Our findings suggest that the current evidence does not adequately support EP is equally safe and effective as CP. In certain selected cases, endoscopic technology has its unique advantages. For patients with strong cosmetic needs, endoscopic or robotic techniques may be an alternative through adequate preoperative evaluations.